Genomics Characterization of an Engineered Corynebacterium glutamicum in Bioreactor Cultivation Under Ionic Liquid Stress - Banerjee, Deepanwita; Eng, Thomas; Sasaki, Yusuke; Srinivasan, Aparajitha; Oka, Asun; Herbert, Robin A.; Trinh, Jessica; Singan, Vasanth R.; Sun, Ning; Putnam, Dan; Scown, Corinne D.; Simmons, Blake; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Corynebacterium glutamicum is an ideal microbial chassis for the production of valuable bioproducts including amino acids and next-generation biofuels. Here we resequence engineered isopentenol (IP) producing C. glutamicum BRC-JBEI 1.1.2 strain and assess differential transcriptional profiles using RNA sequencing under industrially relevant conditions including scale transition and compare the presence vs. absence of an ionic liquid, cholinium lysinate ([Ch][Lys]). Analysis of the scale transition from shake flask to bioreactor with transcriptomics identified a distinct pattern of metabolic and regulatory responses needed for growth in this industrial format. These differential changes in gene expression corroborate altered accumulation of organic acids and bioproducts, including succinate, acetate, and acetoin that occur when cells are grown in the presence of 50mM [Ch][Lys] in the stirred-tank reactor. This new genome assembly and differential expression analysis of cells grown in a stirred tank bioreactor clarify the cell response of a C. glutamicum strain engineered to produce IP.